2011
DOI: 10.3382/ps.2010-01017
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella Typhimurium oral challenge model in mature broilers: Bacteriological, immunological, and growth performance aspects

Abstract: In this study, Salmonella enterica serovar Typhimurium challenge models were tested to identify the best conditions under which to perform the experimental infection of 3-wk-old broilers. Such a model would be useful to study the efficiency of therapeutic treatments that could take place at the end of the grow-out period. Salmonella-free chicks were obtained from a breeder flock vaccinated with Salmonella. Intestinal maternal immunity was monitored by ELISA analyses at 2, 9, and 16 d of age. Data indicated tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
24
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 32 publications
9
24
0
1
Order By: Relevance
“…Infection with Salmonellas leads to a significant negative effect on growth performance of poultry (Vandeplas et al, 2009;Marcq et al, 2011;Wang et al, 2012), which was confirmed in this study. In the present study, there was a significant reduction in BWG after S. typhimurium challenge.…”
Section: Discussionsupporting
confidence: 81%
“…Infection with Salmonellas leads to a significant negative effect on growth performance of poultry (Vandeplas et al, 2009;Marcq et al, 2011;Wang et al, 2012), which was confirmed in this study. In the present study, there was a significant reduction in BWG after S. typhimurium challenge.…”
Section: Discussionsupporting
confidence: 81%
“…The decrease in weight gain might be mainly due to decreased feed intake. Our results was in consistent with previous reports on reduced weight gain and feed intake in poultry challenged with S. gallinarum (Gupta et al, 2005;Vandeplas et al, 2009;Marcq et al, 2011). Our results also demonstrated that the addition of B. subtilis into diets could enhance the growth performance of broilers challenged with S. gallinarum.…”
Section: Discussionsupporting
confidence: 93%
“…We then performed in vivo broiler experiment followed by experimental challenge/infection. Salmonellosis can lead to depression, diarrhea, severe body weight loss, and mortality of poultry (Vandeplas et al, Journal of Poultry Science, 54 (3) Marcq et al, 2011). Infection with S. gallinarum decreased the weight gain compared to unchallenged broilers in this study.…”
Section: Discussionmentioning
confidence: 44%
“…These results corroborate Marcq et al (2011) who demonstrated that after challenge with Salmonella Typhimurium, the birds showed higher titers of secretory IgA.…”
Section: Discussionsupporting
confidence: 91%